The Effect of the Follicle Size and Follicle Number Per Ovary on Oocyte Quality of Local Goat - Sayuti, Arman; Siregar, Tongku Nizwan; Akmal, Muslim; H, Hamdan; H, Hamdani (Universitas Syiah Kuala, 2007)
This research was aimed to find out the relationship between the diameter of follicle and thedifferent of follicle number on oocyte quality of local goat. The oocyte originated from the ovary was takenfrom the Slaughterhouse in Banda Aceh. The ovary was aspirated in the Histology Laboratory ofVeterinary Medicine Faculty of Syiah Kuala University, Banda Aceh. This experiment consisted of twostages, the follicles were selected and divided into 3 groups according to their diameter size. The smalldiameter size 2 mm, medium size 2-5 mm, and big size 5 mm. The second, the ovaries were dividedinto three groups based on number of follicle, i.e; 1(5; 2(6-10); and 3 (11). The diameters of oocytetaken from the three groups of follicle size were measured by using eyepiece micrometer, while the oocytemorphology was categorized into 4 groups. The result of regression data indicated that the biggest folliclediameter yielded the oocyte that had bigger diameter, too. The model of regression is y = 0.955 + 0.157x, y is the diameter of oocyte and x is the diameter of follicle. The close relationship (r) between the diameter offollicle and the diameter of oocyte was 0.967. There are significant differences (P0.05) between the size offollicle and the morphology of oocyte. The oocytes originated from larger follicle tend to have bettermorphological appearance than the oocyte originated from smaller follicle.Keywords: oocyte, follicle